2013
DOI: 10.1016/j.jinorgbio.2013.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific Ni(II)-dependent peptide bond hydrolysis for protein engineering: Active sequence optimization

Abstract: In previous studies we showed that Ni(II) ions can hydrolytically cleave a peptide bond preceding Ser/Thr in peptides of a general sequence RN-(Ser/Thr)-Xaa-His-Zaa-RC, where RN and RC are any peptide sequences. A peptide library screening, assisted by accurate measurements of reaction kinetics for selected peptides, demonstrated the preference for bulky and aromatic residues at variable positions Xaa and Zaa [A. Krężel, E. Kopera, A.M. Protas, A. Wysłouch-Cieszyńska, J. Poznański, W. Bal, J. Am. Chem. Soc., 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…As predicted, Xaa substitutions with Glu or Asp resulted in poorly reactive oligopeptides [107]. The involvement of sterical crowding in the reaction mechanism was confirmed by another peptide library study, which showed that another aromatic residue upstream of Zaa was also beneficial for fast hydrolysis [108]. A study on a series of d-amino acid substituted peptides demonstrated that the stereochemistry of the Ni(II) binding Ser-Arg-His residues is another crucial feature of the reaction (Arg was the most efficient substitution in previous studies) [109].…”
Section: Peptide Bond Hydrolysis In Four-coordinate Square-planar Commentioning
confidence: 55%
“…As predicted, Xaa substitutions with Glu or Asp resulted in poorly reactive oligopeptides [107]. The involvement of sterical crowding in the reaction mechanism was confirmed by another peptide library study, which showed that another aromatic residue upstream of Zaa was also beneficial for fast hydrolysis [108]. A study on a series of d-amino acid substituted peptides demonstrated that the stereochemistry of the Ni(II) binding Ser-Arg-His residues is another crucial feature of the reaction (Arg was the most efficient substitution in previous studies) [109].…”
Section: Peptide Bond Hydrolysis In Four-coordinate Square-planar Commentioning
confidence: 55%
“…This is because the cleavage of the T13-S14 bond leaves the D12-T13 bond in the N-terminal hydrolysis product, decomposing its reactive domain, while the cleavage of the D12-T13 bond yields a 4N Ni(II) complex with the now N-terminal TSH sequence, which locks the T13 and S14 residues in an unreactive conformation. 15,31,34 We detected the expected products of cleavage by ESI-MS for both the model peptide and the protein, but the products of both reactions were too similar to be easily separated and quantified. Therefore, we considered the reactions at these two sites jointly as one cleavage process.…”
Section: Hydrolysis Of Aat and Model Peptidesmentioning
confidence: 98%
“…Nickel hydrolysis has been the subject of extensive investigations in our research group. The conditions chosen for model oligopeptide studies corresponded to previously described experiments on similar peptides ( Protas et al, 2013 ; Podobas et al, 2014 ; Wezynfeld et al, 2014 ). The conditions used for FLG domain had lower total Ni 2+ , but higher Ni 2+ /peptide ratio and were aimed at more accurate mirroring of the skin conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To calculate the rate constants of the acyl shift step ( k 1 ) and the ester hydrolysis step ( k 2 ) of the hydrolysis reaction the set of three equations (Kinet A, Kinet B, and Kinet C) was used, similarly to previous studies ( Kopera et al, 2010 ; Ariani et al, 2013 ; Protas et al, 2013 ). …”
Section: Methodsmentioning
confidence: 99%